Giardiavirus-resistant Giardia lamblia lacks a virus receptor on the cell membrane surface. - Sepp, T (1994)
Giardia lamblia virus (GLV) is a small nonenveloped double-stranded RNA virus that infects specifically the parasitic protozoan G. lamblia. Among the many collected strains of G. lamblia, a few turn out to be highly resistant to the virus infection. Two of these strains, Ac and JH, were subjected to electroporation with the RNA from GLV-infected G. lamblia WB strain. Subsequent studies indicated the presence of GLV double-stranded RNA and GLV protein in the electroporated and propagated cells. Virus particles, released by the transfected cells into the culture medium, were capable of infecting the virus-sensitive G. lamblia WB strain. When the WB cells were incubated with GLV at 4 degrees C and treated with the bifunctional cross-linking reagent disuccinimidyl suberate, little GLV protein was detectable inside the cells by immunofluorescent staining. However, patches of fluorescent granules were found on the membrane surface of the cells, suggesting cross-linking of the viruses with a certain membrane component(s). Similar treatment of the resistant strains Ac and JH showed no fluorescence either inside or outside of the cells. Two other closely related parasitic protozoa, Tritrichomonas foetus and Trichomonas vaginalis, cannot be infected by GLV via either viral infection or RNA transfection. The [35S]cysteine-labeled protein profiles in Triton X-114 extracts of G. lamblia WB, Ac, and JH were compared. The profile of the WB strain differs clearly from that of Ac and JH. It remains to be seen, however, whether this difference is related at all to the different susceptibilities to GLV infection.